2017
DOI: 10.3389/fphar.2017.00723
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Omega-3 Fatty Acids Supplementation Accelerates Nerve Regeneration and Prevents Neuropathic Pain Behavior in Mice

Abstract: Fish oil (FO) is the main source of long chain omega-3 polyunsaturated fatty acids (ω-3 PUFAs), which display relevant analgesic and anti-inflammatory properties. Peripheral nerve injury is driven by degeneration, neuroinflammation, and neuronal plasticity which results in neuropathic pain (NP) symptoms such as allodynia and hyperalgesia. We tested the preventive effect of an EPA/DHA-concentrate fish oil (CFO) on NP development and regenerative features. Swiss mice received daily oral treatment with CFO 4.6 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…Peripheral nerve injury is followed by a cascade of pathophysiological events, including the disorganization of the blood–nerve barrier, the recruitment of circulating macrophages, proliferation of Schwann cells, raised cytokine production, the rearrangement of endoneurial place and production of extra cellular components . Moreover, axonal count after 2 weeks of sciatic nerve injury has been found to increase in mice treated with concentrate fish oil containing EPA and DHA, which supports our finding in the regeneration index at 21 days after CCI.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Peripheral nerve injury is followed by a cascade of pathophysiological events, including the disorganization of the blood–nerve barrier, the recruitment of circulating macrophages, proliferation of Schwann cells, raised cytokine production, the rearrangement of endoneurial place and production of extra cellular components . Moreover, axonal count after 2 weeks of sciatic nerve injury has been found to increase in mice treated with concentrate fish oil containing EPA and DHA, which supports our finding in the regeneration index at 21 days after CCI.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, our study supports evidence that fish oil enriched in omega‐3 fatty acids administration produce earlier improvement of pain‐related behaviours than motor functional recovery. As mentioned before, Silva et al . found that omega‐3 administration prevents mechanical allodynia and thermal hyperalgesia in the first 5 days after nerve injury.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, the contribution of DHA depletion to the disease remains largely uncharacterized. Alternatively, previous work on DHA metabolism and neurodegeneration demonstrates a positive role of this lipid in Parkinson's disease [13], neuroinflammation [14], cognitive impairment [15], Alzheimer's disease [16], and neuropathic pain [17]. Previously, we showed that a general change in polyunsaturated fatty acid content in diets could influence disease evolution in the B6SJL-Tg (SOD1-G93A)1Gur/J transgenic mice [18].…”
Section: Introductionmentioning
confidence: 92%